La voz del pueblo : periódico liberal e independiente, publicado bajo los auspicios de la Sociedad Rodríguez (Independent Mexico in newspapers, the 19th century ;)
Some issues include a list of Mexicans owning land in Texas, county where land is located, size in leagues and year granted.